Efektivitas Yoga Terhadap Peningkatan Kualitas Hidup ODHA di Bali - I Made Sugata; Putu Emy Suryanti; Made G. Juniartha; Ni Luh Arick Istriyanti (Jayapangus Press, 2022)
The purpose of this research is to know the effectiveness of yoga on the quality of life of people living with HIV/AIDS (PLWHA). This research is a quantitative research that uses a pre-experimental method through a one group pretest-posttest design approach. The sample in this study was PLWHA in Bali Province who actively participated in the activities and were willing to become research respondents with a total of 18 respondents. The sampling technique used is purposive sampling technique. The instrument or measuring instrument in this study is the WHOQOL-HIV BREF questionnaire which is the standard instrument from WHO to obtain perceptions of the quality of life of PLWHA. The data analysis carried out was univariate analysis and bivariate analysis. Based on the results of univariate analysis, it was found that an increase in the quality of life of respondents after being given yoga practice as indicated by the greater minimum and maximum values ​​in the posttest scores compared to the pretest scores (91-107 > 107-134) and supported by the mean value of the posttest results which showed the results greater (116.44) than the mean pretest value (98.72). The results of the bivariate analysis showed the difference in the pretest and posttest scores on the quality of life scale of PLWHA of 0.000 which showed a significant difference between the respondents' quality of life scores before and after yoga practice and the value of the effectiveness of yoga practice on the quality of life of PLWHA was 0.88, which indicates that yoga practice has great effectiveness in improving the quality of life of PLWHA in Bali Province.